Chemoradiation in patients with isolated recurrent pancreatic cancer - therapeutical efficacy and probability of re-resection - Habermehl, Daniel; Brecht, Ingo C.; Bergmann, Frank; Welzel, Thomas; Rieken, Stefan; Werner, Jens; Schirmacher, Peter; Buechler, Markus W.; Debus, Juergen; Combs, Stephanie E. (Radiation Oncology, 2013)
Background: In the present retrospective analysis we analysed the therapeutic outcome of a set of patients, who were treated with chemoradiation (CRT) for recurrent pancreatic cancer (RPC) in a single institution.Patients and Methods: Forty-one patients had a history of primary resection for pancreatic cancer. In case of an unresectable recurrency patients were treated with CRT at our institution between 2002 and 2010 with a median dose of 48.4 Gy (range 39.6-54 Gy). Concurrent chemotherapy regimes included Gemcitabine (GEM) in 37/41 patients (90%) and Fluorouracil (FU) or Capecitabine (CAP) in 4/41 patients (10%). Patients were re-evaluated after CRT with computed tomography and/or explorative laparotomy. During re-resection or laparotomy 15 patients received an additional intraoperative radiotherapy (IORT) with a median dose of 15 Gy (range 12-15 Gy). Median age was 65 years (range 39-76 years) and there were 26 male and 15 female patients.Results: The median overall survival (mOS), local control (LC) and progression-free survival (PFS) were 16.1, 13.8 and 6.9 months respectively for all patients after the first day of CRT. Re-resection was possible in five patients (12%) and a complete remission (CR) as defined by tumor-free biopsy was seen in 6 patients (15%). When re-resection could be achieved after CRT mOS was improved to 28.3 months (n = 5 patients, 95%-CI 10.2 - 46.3 months). Patients receiving IORT had a significantly improved mOS compared to no IORT (p = 0.034). Fifteen patients (37%) experienced a local tumour progression and main site of distant metastasis was the liver (11 patients, 27%).Overall treatment-related toxicity was mild, grade III hematologic toxicity was observed in 11 patients (27%). Conclusion: In summary we observed a good therapeutic response with mild to moderate toxicity levels for CRT in RPC. Overall survival and PFS were clearly improved in case of induction of a complete remission (tumor-free biopsies) or after achieving a re-resection, thus providing a curative intended therapy even in case of disease recurrence. © 2013 Habermehl et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2023-03-08